The use of Kinesiology Taping among people aged between 25 and 55 with the non-specific pain of spine in its lumbar and sacral part - Bartosz Kochański; Krystian Kałużny; Anna Kałużna; Michał Cichosz; Sławomir Gałęcki; Magdalena Hagner-Derengowska; Xawery Zukow (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
INTRODUCTION. The phenomenon of the pain ailments of spine is very complex and increasingly common. The key aspect of the treatment is the appropriate choice of the therapy, which may be dependent on many factors i.e.: the cause of the ailments, the phase of the disease, the clinical sypmtoms, the general health condition of the patient, the functional disorders and the patient's abbilities. AIM OF THE RESEARCH. The aim of the research is the assessment and the comparison of the effects of two methods of the treatment: 1) the therapy based on general exercises focused on the lumbosacral spine combined with Kinesiology Taping and 2) the therapy based on general exercises focused on the pain intensisty and on the life quality of people with chronic, non-specific pain of the lumbosacral spine among patients aged 25-55. MATERIALS AND METHODOLOGY. The research was conducted in a group of 50 people with chronic spine pain in the lumbosacral area. They were randomly divided into two groups: 1) the study group, where the ligament application of Kinesiology Taping was used for seven days (KT+GE), 2) the control group: no appliation of Kinesiology Taping (GE). Both groups took general exercises commonly used in the treatment of non-specific pain ailments of the lumbosacral spine for seven days. Durring the assessment of the effectiveness of the therapy the NRS scale (Numerical Rating Scale)and the Oswestry Low Back Pain Disability Scale questionnaire were used. RESULTS. At the end of the treatment in the KT+GE group the decrease of the average pain intensity was observed from 6,20 to 2,12 (median 6,00 vs 2,00). The decrease of the average pain intensity was also noted in the GE group from 6,20 to 3,48 (median 6,00 vs 4,00). The statistical analysis showed that both forms of the therapy had a statistically significant impact (p<0,05) on the decline of the pain intensity in the NRS scale among the patients with the pain ailments of the spine in the lumbar and sacral area. In the KT+GE group after the therapy the decrease was observed: the average from 19,20 to 8,12 and median from 17,00 to 8,00. In the GE group the decrease was also noted: the average from 20,28 to 10,80 and median from 19,00 to 10,00. The statistical analysis showed that both forms of the therapy had a beneficial and statistically significant -p<0,05 impact on the ODI sum variable among the patients with the pain in the lumbosacral part. CONCLUSIONS. 1. Both forms of the therapy influenced statistically significantly on the decrease of the pain intensity in the NRS scale among the patients with the pain ailments in the lumbosacral spine. However, the therapy during which the Kinesiology Taping was implemented was statistically significantly more effective. 2. Both forms of the therapy influenced statistically significantly on the improvement of the quality of life among the patients suffering from the lumbosacral pain. However, the therapy during which the Kinesiology Taping was implemented was statistically significantly more effective.